Patrones distintivos de deposición de calosa proveen evidencia temprana de aborto de óvulos en el arbusto andromonoico Caesalpinia gilliesii - Calviño, Ana Alejandra (2009)
Ovule abortion may lead to the partial or complete reduction of the number of functional ovules in the ovary and then is the primary factor that determines the sexual expression of the plant. In different species, ovule abortion was associated with the presence of callose in advanced ovules. Based on these observations, we studied the pattern of ovule development and callose deposition in both perfect and staminate flowers of the andromonoecious shrub Caesalpinia gilliesii. The obtained results showed that all ovules reached the 8-nucleate stage of embryo sac development and exhibited callose deposition at advanced stages. Nevertheless, from the 2-nucleate stage, a distinct spatial pattern of callose deposition within the ovule was observed between perfect and staminate flowers. Differences in callose deposition suggest that not callose per se but its distribution pattern in the ovule tissues is the main factor that triggers ovule isolation and abortion and leads to flowers with non-functional pistils in this species. Furthermore, previous observed differential growth rates between perfect and staminate flowers support for resource depletion as the likely underlying mechanism of ovule fate in C. gilliesii.